1979-1980 ネン マクマードサウンド チイキ オヨビ エルスワース サンチ ノ コクサイ キョウドウ カンソク ホウコク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1981)
P(論文) 1979-80年の南極の野外調査期間, マクマードサウンド地域において, 日本隊は次の観測・調査を実施した。1)エレバス火山山頂での地震観測。2)アランヒルズ裸氷帯での氷河観測。3)エルスワース山地の地質調査。4)マクマードサウンドの堆積層とテクトニクスの国際共同研究への参加。1)∿3)のプロジェクトは日米共同で, 4)はニュージーランドが中心であった。この中で1)と2)は, 日米がほぼ対等の条件で観測・調査を実施したのに対し, 3)と4)は, アメリカまたはニュージーランド隊に日本も参加する形となった。1979年11月28日, ニュージーランド航空の南極観光機DC-10が, エレバス山山麓に墜落し, この事故処理のため, それぞれの計画が大幅に変更された。日本隊関係のプロジェクトも観測期間の短縮, 調査地域の縮小などがあったが, 所期の目的は達成された。 The Japanese party consisting of seven members participated in projects for the McMurdo Sound region and the Ellsworth Mountains from October 20th, 1979 to January 23rd, 1980. The main projects of this season were : seismological observations at the summit of Mount Erebus; glaciological survey in the Allan Hills bare ice field; geological survey in the Ellsworth Mountains; and Mc Murdo Sound Sediments and Tectonics Study (MSSTS). The first three projects were carried out in cooperation with the United States. The last one was an international project organized by the New Zealand Antarctic Research Program (NZARP). An aircraft crash on the Mount Erebus, which occurred on November 28,1979,forced to curtail the projects by the United States Antarctic Research Program and NZARP, however the Japanese projects were completed with satisfaction. departmental bulletin paper